Molecular dynamics simulation of the gramicidin channel in a phospholipid bilayer. - Woolf, T B (1994)
A molecular dynamics simulation of the gramicidin A channel in an explicit dimyristoyl phosphatidylcholine bilayer was generated to study the details of lipid-protein interactions at the microscopic level. Solid-state NMR properties of the channel averaged over the 500-psec trajectory are in excellent agreement with available experimental data. In contrast with the assumptions of macroscopic models, the membrane/solution interface region is found to be at least 12 A thick. The tryptophan side chains, located within the interface, are found to form hydrogen bonds with the ester carbonyl groups of the lipids and with water, suggesting their important contribution to the stability of membrane proteins. Individual lipid-protein interactions are seen to vary from near 0 to -50 kcal/mol. The most strongly interacting conformations are short-lived and have a nearly equal contribution from both van der Waals and electrostatic energies. This approach for performing molecular dynamics simulations of membrane proteins in explicit phospholipid bilayers should help in studying the structure, dynamics, and energetics of lipid-protein interactions.